The role of support advocates: a case study - Redic, Connie L. (My University, 2024)
This qualitative case study examined the role of three support advocates in an urban middle school setting when working with tier 3 students. Support advocates are support staff members who work with a specific caseload of students- identified because they are at risk of early drop out from high school- but defining their role as a wraparound intervention is necessary because of this approach to an intervention outside of the classroom setting. Bronfenbrenner’s Socio-Ecological Framework and the Self-Advocacy Theory grounded this work, supporting the premise that a student’s environment (and the adults within it) can have effects on their growth and development. Through semi-structured interviews of support advocates and six students, field observations, and online surveys submitted by 16 teachers of the students, the role of support advocates and their potential outcomes with students was investigated as an MTSS-like strategy of support (i.e. Multi-Tiered System of Supports). Data suggested support advocates provide varying support to multiple stakeholders including academic, behavioral, and social interventions. Findings suggested support advocates may be an effective arm of schoolwide improvement and intervention programs. The key findings of this study will allow educational practitioners and school and district leaders MTSS intervention evidence for student supports outside of the classroom.
Keywords: Socio-emotional; Support advocate; Multi-Tiered System of Supports (MTSS); Response to Intervention (RTI); Intervention; Relationships